Information Support Complex for Studying the Reliability of Work of Continuous Cooperation System Operator Under Increased Situational Stress - Aralova, N.I. (Science and Innovation, 2024)
To research the reliability of operator’s work under heightened situational stress, the weak link model has been proposed. Software has been designed to study the work reliability of military transport drivers and pilots under heightened situational stress.